Are preterm birth and very low birth weight rates altered in the early COVID (2020) SARS-CoV-2 era? - Rodriguez, Kayla; Nudelman, Matthew J.; Jegatheesan, Priya; Huang, Angela; Devarajan, Kamakshi; Haas, Jessica E.; Cervantes, Rosemarie; Falbo, Kelle; Narasimhan, Sudha Rani; Cormier, Machelnil; Stewart, Mary Beth; Patel, Rupalee; et al. (Frontiers in Pediatrics, 2023)
Objective: We evaluated the prevalence of preterm birth (PTB) and very low birth weight (VLBW) during Jan-Dec 2020 (early COVID era) at 5 hospitals (2 in West Virginia, 3 in California) compared to Jan 2017-Dec 2019 (pre-COVID) inclusive of 2 regional perinatal centers (1 in Huntington, WV and 1 in San Jose, CA) and 3 community hospitals (1 each in Cabell, Los Angeles and Santa Clara counties). Design/Methods: We examined PTB and VLBW rates of live births at 5 US hospitals from Jan 2017-Dec 2020. We compared PTB and VLBW rates in 2020 to 2017-2019 using Poisson regression and rate ratio with a 95% confidence interval. We stratified live births by gestational age (GA) (<37 weeks, 33-36 weeks, and <33 weeks) and birth weight (< 1500g, >1001g-< 1500g, < 1000g). We examined PTB rates at 4 of the hospitals during Jan-Dec 2020 and compared them to the prior period of Jan 2017-Dec 2019 using Statistical Process Control (SPC) for quarterly data. Results: We examined PTB and VLBW rates in 34,599 consecutive live births born Jan 2017-Dec 2019 to rates of 9,691 consecutive live births in 2020. There was no significant change in PTB (<37 weeks GA) rate, 10.6% in 2017-2019 vs 11.0% in 2020 (p=0.222). Additionally, there was no significant change when comparing VLBW rates in 2017-2019 to 2020, 1.4% in 2017-2019 vs 1.5% in 2020 (p=0.832). However, the regional NICU in San Jose, California showed an increase in ELBW (<1000g) from 0.4% in 2017-2019 to 0.8% in 2020 (p=0.013).